Birokrasi Weberian: “Proportional Approach” - Midkholus Surur (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2019)
Weberian bureaucracy theory is a bureaucratic theory that is very influential on allcountries both those who embrace democracy and authoritarianism. Weber sees thatbureaucratic performance can be approached from social behavior theory. To know andexplain human behavior, it must first know the intent and purpose of the behavior. Weberdistinguishes the motives behind human behavior, namely affective, traditional, value rationaland instrumentally rational. Instrumentally rational is the guideline in the behavior ofWeber's bureaucracy. Weber further stated, authority is not formed and implemented byitself. In order to create a legal authority there are five creeds that must be used as guidelines.The five creeds are as follows: Legitimate rules, law is an abstract, impersonal system of rules,which obeys the law only as members of the bureaucracy, obedience not to the person holdingauthority but to the impersonal rule of law. Based on the five conceptions, Weber formulatedeight propositions regarding the formulation of legal authority namely: official dutyregulation, task specialization, hierarchical, technical-legal, impersonal, written,administrative-bureaucratic staff. This theory is considered by many political experts andgovernments to have a number of weaknesses. These weaknesses are a hierarchicalbureaucratic structure, a military-like organizational system, excessive emphasis on the legalformal aspect, unit specialization, bureaucratic employees who are not neutral andbureaucratic employees who are less representative. Besides these weaknesses, Weber'sbureaucratic theory has made a positive contribution in the process of implementinggovernance today, namely the impersonal system, the contract system for employees, thecareer system and the focus on one position.